Job : the faith to challenge God : a new translation and commentary - Brown, Michael L., 1955-; Brown Michael L.; JOB: The Faith To Challenge God: A New Translation And Commentary (Peabody, Massachusetts : Hendrickson Academic, 2019)
"A new translation and commentary on the biblical book of Job with exegetical essays and theological reflections on key themes and passages"--
Includes bibliographical references (pages [431]-438).
Keywords: Brown Michael L; Bible. -- Commentaries